Anthropometric and performance characteristics of the German rugby union 7s team - Hohenauer, E.; Rucker, A. M.; Clarys, P.; Küng, U. M.; Stoop, R.; Clijsen, R. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Somatotyping is advantageous in sports for the optimal development of performance level and injury prevention. The aim of this study was to describe the anthropometric and physical performance characteristics of the German national rugby union 7s team. Seventeen male rugby players, classified as forwards (N.=9; 24.2±2.1 years) and backs (N.=8; 24.3±5.05 years) were assessed.